2021
DOI: 10.3892/or.2021.8220
|View full text |Cite
|
Sign up to set email alerts
|

Platelet isoform of phosphofructokinase accelerates malignant features in breast cancer

Abstract: The platelet isoform of phosphofructokinase (PFKP) is one of the key enzymes in the glycolytic pathway. PFKP is highly expressed in several cancers, and it has been reported to be involved in the progression of cancer cells. However, its oncological role in breast cancer (BC) remains unclear. The present study aimed to evaluate the function of PFKP in BC cells and its expression level in patients with BC. Firstly, the mRNA and protein expression of PFKP was evaluated in BC and non-cancerous mammary cell lines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Consequently, we next aimed to assess the functional impact of representative lysine–meroterpenoid interactions on target proteins. Proteins crucial to metabolic pathways that are essential for breast cancer progressionnamely, lipid metabolism (ABHD12), mitochondrial respiration (IDH2), and glycolysis (PFKP, PFKM, PFKL), , were chosen not only for their individual roles but also for their interplay with the mechanisms that regulate mitochondrial dynamics.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Consequently, we next aimed to assess the functional impact of representative lysine–meroterpenoid interactions on target proteins. Proteins crucial to metabolic pathways that are essential for breast cancer progressionnamely, lipid metabolism (ABHD12), mitochondrial respiration (IDH2), and glycolysis (PFKP, PFKM, PFKL), , were chosen not only for their individual roles but also for their interplay with the mechanisms that regulate mitochondrial dynamics.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Wang et al reported that PFKP overexpression inhibited cancer cell apoptosis and accelerated the growth, migration, and invasion of H1299 cells [33]. In breast cancer, PFKP expression was negatively correlated with estrogen receptor and human epidermal growth factor receptor-2 and positively correlated with transforming growth factor-β and MYC expression [34]. A study reported that PFKP expression was positively associated with estrogen receptor-and progesterone receptor-negative breast cancers [29].…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that PFKP expression was positively associated with estrogen receptor-and progesterone receptor-negative breast cancers [29]. Decreased PFKP expression significantly suppressed breast cancer cell growth and invasion [34]. A dietary polyphenolic compound, quercetin, suppressed growth and migration by inhibiting PFKP and LDHA expression in breast cancer [29].…”
Section: Discussionmentioning
confidence: 99%
“…PFKP is gaining attention for its significant role in BC progression. Highly expression of PFKP was observed in estrogen receptor‑negative and human epidermal growth factor receptor (EGFR) 2‑negative BC cell lines [26] and human BC tissues [25] . The knockdown of PFKP significantly attenuated the proliferation and invasiveness in MCF7, SK‑BR‑3, and MDA‑MB‑231 BC cells [26] , and the role of PFKP in promoting tumor progressive oncology was speculated to be clearly related to transforming growth factor‑β1 and MYC proto‑oncogene [26] .…”
Section: Glycolysismentioning
confidence: 99%
“…Highly expression of PFKP was observed in estrogen receptor‑negative and human epidermal growth factor receptor (EGFR) 2‑negative BC cell lines [26] and human BC tissues [25] . The knockdown of PFKP significantly attenuated the proliferation and invasiveness in MCF7, SK‑BR‑3, and MDA‑MB‑231 BC cells [26] , and the role of PFKP in promoting tumor progressive oncology was speculated to be clearly related to transforming growth factor‑β1 and MYC proto‑oncogene [26] . Not only the foregoing, but the high expression of PFKP associated with the increased PFKP S386 phosphorylation was identified in Wnt signaling‑induced BC development in a β‑catenin‑independent manner [27] or the activation of Kru¨ppel-like factor in BC cells [28] .…”
Section: Glycolysismentioning
confidence: 99%